Peace, Justice and International Order - Förster, A. author. aut Link
XV, 185 p.
Keywords: How can fair cooperation and a stable peace be reached in the international realm? Peace, Justice and International Order discusses this question in the light of John Rawls' The Law of Peoples, offers a new approach to Rawls' international theory and contributes to the discourse on international peace and justice.